Implementation of Research Based Learning Development in Maternity Nursing Course - Indah Lestari; Noer Saudah; Catur Prasatia Lukita Dewi (Humanistic Network for Science and Technology (HNST), 2020)
There have been many learning innovations that have been carried out by lecturers, but there are still many that only emphasize the low-level cognitive domains and not the high-level cognitive domains (analysis, synthesis, evaluation, and creation), the affective and psychomotor domains. The learning model has not been used many facilitate students to learn actively. As a result, learning is more dominated lecturers so that student activities are less than optimal. The purpose of this study is to develop learning tools and textbooks maternity nursing courses with a research-based learning approach. The resulting product are (1) learning tools in maternity nursing and (2) textbooks with research-based applications. The research was conducted on 40 undergraduate students of STIKes Bina Sehat PPNI Mojokerto, who carried out the academic learning process of maternity nursing. The method used refers to the 7 stages of the research-based learning process, with the validation of consultants and education experts. The main framework above is used as a basis for developing learning tools. Then the expert test of theoretical validity was carried out on the implementation of the RBL learning tool, with the result that the value of r = 0.909 (high reliability). The test results are widespread, not much different from the expert test results. While research-based textbooks are the results of research outputs, used as a guide for students to be able to build critical thinking, analysis and structure based on evidence. Keywords: research based learning; learning tools; maternity nursing